Perancangan Aplikasi Stegakrip Dengan Metode LSB Dan Algoritma RSA Berbasis Web - Rohmat Nur Ibrahim; Ilham M.S. (STMIK Mardira Indonesia, Bandung, 2017)
Security is necessary especially in maintaining data or information that is private and confidential. For that required a data security with the aim of keeping the data so that can not be accessed by parties who do not have rights. Based on the above information is made a stegakrip application where the stegakrip is a combination of two words of steganography and cryptography. Where cryptography is the art of keeping messages safe when messages are sent from one place to another. While steganography is an art of hiding secret messages on a medium in such a way that no one suspects the existence of hidden messages. In this application stegakrip used LSB (Least Significant Bit) method which is a steganography method where a data is hidden into an object such as images where the bits are less meaningful in the picture is reordered as a place of data insertion. As for cryptography in this application used RSA algorithm (Rivest, Shamir, Adleman) which is one of asymmetric cryptography algorithm where the key for encryption is different with the key used to decrypt a data. Other means as a comparison for cryptography provided encryption with AES (Advanced Encryption Standard) algorithm and Hash function. Keywords: stegowrip, steganography, cryptography.